2016
DOI: 10.5021/ad.2016.28.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Onychomatricoma: A Rare Tumor of Nail Matrix

Abstract: Onychomatricoma is a rare tumor of the nail matrix. Until now, few cases of onychomatricoma have been reported in the literature. Immunohistochemically, CD10, a marker of the onychodermis, is expressed in the stroma of the onychomatricoma. In the present case, a 27-year-old woman presented with an 8-year history of a yellowish, thickened, and overcurved nail plate of the right index finger, mimicking onychomycosis. She had been treated for 4 years with antifungal agents by general physicians, without improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…In the other four cases, longitudinal oblique US image of the nail evidenced hypoechogenic solid areas affecting the nail matrix (under the proximal nail fold) with hyperechogenic linear dots corresponding to the finger‐like tumoral projections deforming the plate. Analysis with colour Doppler US showed a non‐specific hypovascular pattern . In our experience, axial images of the tumoral digitations can be obtained at the free edge margin of the nail plate (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In the other four cases, longitudinal oblique US image of the nail evidenced hypoechogenic solid areas affecting the nail matrix (under the proximal nail fold) with hyperechogenic linear dots corresponding to the finger‐like tumoral projections deforming the plate. Analysis with colour Doppler US showed a non‐specific hypovascular pattern . In our experience, axial images of the tumoral digitations can be obtained at the free edge margin of the nail plate (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Ultrasonography (US) is an imaging technique that uses reflected pulses of high‐frequency sound waves and can be used to assess soft tissues. Six onychomatricomas were evaluated by high‐resolution variable‐frequency US . In two cases, ultrasound imaging failed to provide diagnostic evidence of the disease .…”
Section: Resultsmentioning
confidence: 99%
“…Dermoscopy typically shows perforations in the distal portion of the nail plate, haemorrhagic striae, and white longitudinal grooves corresponding to the nail plate channels [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…CD10 is expressed in onychomatricoma and may also be used as a marker to define excision specimens of the nail in ingrown nail surgery. 10,11 Patchy weak expression of CD10 and CD34 was seen in a rare case of unguioblastic matrix fibroma. 12 While the concept of onychodermis was rejected, at least for adult nails, by Perrin on the basis that he found less consistent CD10 marking and focal CD34 expression, 13 others assume that the onychodermis might play a role in the production and adhesion of the hard keratins of the nail plate.…”
mentioning
confidence: 98%
“…Although the enzyme function of CD10 is clearly defined and many cells and tissues are identified that contain CD10, it is yet unknown what CD10 exactly does in the nail matrix and bed connective tissue. CD10 is expressed in onychomatricoma and may also be used as a marker to define excision specimens of the nail in ingrown nail surgery . Patchy weak expression of CD10 and CD34 was seen in a rare case of unguioblastic matrix fibroma .…”
mentioning
confidence: 99%